Cancers due to excess weight, low physical activity, and unhealthy diet: estimation of the attributable cancer burden in Germany - Behrens, Gundula; Stock, Christian; Brenner, Hermann; Mons, Ute (Deutsches Ärzteblatt, 2018)
BACKGROUND: Excess weight, low physical activity, low intakes of dietary fiber, fruits, and vegetables, and high meat and salt intake increase cancer risk. - METHODS: Numbers and proportions (population-attributable fractions, PAF) of incident cancer cases in Germany in 2018 attributable to these factors were estimated by sex and age groups for ages 35 to 84 years using population projections, national cancer incidence and exposure data, and published risk estimates. - RESULTS: Estimated numbers (percentages) of attributable cancers were 30 567 (7%) for excess weight, 27 081 (6%) for low physical activity, 14 474 (3%) for low dietary fiber intake, 9447 (2%) for low fruit and vegetable consumption, 9454 (2%) and 1687 (0.4%) for processed meat and high red meat consumption, respectively, and 1204 (0.3%) for high salt intake. Excess weight substantially contributed to endometrial, renal, and liver cancer (PAF = 24 to 35%). Low physical activity contributed to endometrial, renal, and lung cancer (PAF = 15 to 19%), and dietary factors mainly contributed to colorectal, breast, and lung cancer (PAF = 9 to 16%). - CONCLUSION: A considerable proportion of cancer cases are attributable to excess weight, physical inactivity, and unhealthy dietary habits. Major prevention efforts are needed to reduce the cancer incidence attributable to these avoidable factors.
Gesehen am 14.11.2018